THE ROLE OF SERVICE AND RELATIONSHIP QUALITY TOWARD CUSTOMER SATISFACTION AND LOYALTY IN BANK JATENG BRANCH OF SURAKARTA - Tri Nurdyastuti; I Gusti Putu Diva Awatara (MESP–FEB UNS, 2018)
The purpose of this study to know effect of service quality and relationship to customer satisfaction and customer loyalty in Bank Jateng Branch Surakarta. Total sample of 100 respondents are customers of Bank Jateng Branch of Surakarta. The data in this research will be obtained directly from the results of interviews with the spread of questionnaires that have provided answers and or from field observations. Data showing the intensity of a behavior, a qualitative quantity will be quantized by using Likert scale. The result of regression equation shows that: Service quality significantly influence customer satisfaction at Bank Jateng Branch of Surakarta. Relationship significant effect on customer satisfaction at Bank Jateng Branch Surakarta. Service quality significantly affects customer loyalty in Bank Jateng Branch of Surakarta. Relationship significant effect on customer loyalty in Bank Jateng Branch Surakarta. Customer satisfaction has no significant effect on customer loyalty in Bank Jateng Branch of Surakarta. The conclusion of this path analysis shows that the use of intervening variable of customer satisfaction in order to increase loyalty, for the variable of service quality and relationship shows ineffective.Keywords: Service Quality, Relationship, Customer Satisfaction, Loyalty